Chaos May Prevail Without Filial Piety: A Cross-Cultural Study on Filial Piety, the Dark Triad, and Moral Disengagement - Qiao, Xiuqing; Lv, Yiqing; Aldbyani, Aamer; Guo, Qingke; Zhang, Tianyi; Cai, Minghang (Frontiers in Psychology, 2021)
In traditional Chinese society, filial piety (FP) served as the philosophical foundation of social governance, without which chaos would prevail. It indicates that the function of FP is not limited to family. FP can predict attitudes and behaviors in other social contexts. This study examined the relationship between FP and moral disengagement, and the mediating roles of the dark triad personality, and cultural differences regarding these mechanisms. An online self-report survey was conducted in two different culture groups- university students from China (N=400, 37% male, M age = 20.41, SD age =2.52) and Islamic countries who are studying in China (N=378, 59.25% male, M age = 24.29, SD age =4.77). Correlation analysis showed that authoritarian FP was positively associated with moral disengagement among students from China and Islamic countries, while reciprocal FP only negatively correlated with moral disengagement among Chinese students. Moreover, reciprocal FP directly and negatively affected moral disengagement, and did so indirectly through the mediating role of Machiavellianism. However, authoritarian FP directly and positively influenced moral disengagement, and did so indirectly through the buffering role of narcissism. These two parallel mediating models are not affected by culture. Though FP varies from culture to culture, reciprocal FP and authoritarian FP play critical roles in influencing personality and moral development. Reciprocal FP reduces moral disengagement directly and indirectly by weakening Machiavellianism. The role of authoritarian FP is conflicting. It can strengthen moral disengagement, but may also weaken it by deterring the development of the narcissistic personality. The findings enlighten us to view authoritarian FP dialectically. These two parallel mediating models are not affected by culture, indicating the applicability of DFPM in other societies. Future studies are encouraged to involve participants from more divergent countries and cultural backgrounds.